13 Anticipated RPGs for 2011 and beyond. - Herring, Will.
A look at over a dozen promising role-playing games on the horizon
Keywords: Pokémon (Game); Deus Ex: Human Revolution (Game).; Torchlight (Game).; Kingdom of Amalur (Game).; Role-playing games (RPG).